Management Challenges in a Child with Chronic Hyponatremia: Use of V2 Receptor Antagonist. (9th January 2017) - Krishnan, Sowmya; Deshpande, Swapna; Mallappa, Ashwini; Divya, Gunda; Lane, Pascale; Vishwanath, Anu; McNall-Knapp, Rene Y.
Abstract : Chronic hyponatremia is very rare in children and is often seen in the setting of congestive heart failure or liver failure in adults. Here, we report an 8-year-old child with hypothalamic glioma who presented with severe hyponatremia. Initial management consisted of fluid restriction. This was very difficult for the child to follow and the child developed bizarre drinking habits requiring intervention from child psychiatry. So therapy was initiated with low dose V2 receptor antagonist under close inpatient monitoring. While initial response was reassuring, her sodium levels tended to drift down with longer duration of treatment requiring us to increase the dose frequently. Her response to therapy and her stable clinical situation off therapy suggest that she may have reset osmostat.